Avaliação pedagógica para alunos surdos no contexto de um programa inclusivo bilíngue - Resende, Alice Almeida Chaves de (2015)
The current educational policy postulates the inclusion of all children at regular schools, respecting their needs and peculiarities. However, such care is not always provided. Due to language access difficulties, the deaf students are excluded from the teachinglearning processes. It is extremely important to develop pedagogical practices focused at these individuals‟ needs. These initiatives should facilitate the acquisition and use of Brazilian Sign Language (Libras) at school. Actions toward this goal became mandatory with the publication of the Brazilian Federal Decree 5.626/05. This study is articulated to a schooling program called Inclusive Bilingual Program, which conducts researches and follow-up actions as part of an inclusion program for deaf students at a regular school in São Carlos/SP. Its main focuses are to develop the bilingual education for deaf students and to insert Libras at school environment, applying appropriate methodologies and teaching practices. The aim of this work is to propose an evaluation system for deaf students written language analysis and follow-up, focused at Libras users. Three studies were carried out in order to create, test and apply the evaluation system proposed. The performance of each student was analyzed concerning their Portuguese Language registers. This study can contribute to the educational system, which needs instruments to evaluate its aims, actions and strategies for supporting the bilingual education of deaf people.